2004
DOI: 10.1160/th03-08-0572
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Gla protein is associated with coronary artery calcification as assessed by electron-beam computed tomography

Abstract: Matrix Gla protein (MGP) is an extracellular matrix protein with wide tissue distribution. It has been demonstrated that the expression of MGP is detected not only in the normal blood vessels but also calcified atherosclerotic plaques, and that MGP deficient mice develop extensive arterial calcification. MGP is thought to be a regulator of vascular calcification. A recent clinical study demonstrates the association between polymorphisms of the MGP gene and increased risk of myocardial infarction. However, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(42 citation statements)
references
References 25 publications
2
39
1
Order By: Relevance
“…Numerous studies have confirmed that MGP is a calcification inhibitor, and alterations in circulating levels of MGP have been observed in different populations characterized by vascular calcification [13,[21][22][23]. In this study, we show markedly enhanced plasma levels of dp-cMGP and in particular of dp-ucMGP in patients with symptomatic AS.…”
Section: Discussionsupporting
confidence: 75%
“…Numerous studies have confirmed that MGP is a calcification inhibitor, and alterations in circulating levels of MGP have been observed in different populations characterized by vascular calcification [13,[21][22][23]. In this study, we show markedly enhanced plasma levels of dp-cMGP and in particular of dp-ucMGP in patients with symptomatic AS.…”
Section: Discussionsupporting
confidence: 75%
“…It provides the binding site of MGP to calcium. Reports on correlations between unphosphorylated MGP serum levels and coronary calcification scores have been conflicting [17,18,29]. Recently, ucMGP also failed to show a correlation with markers of vascular stiffness in children on dialysis [30].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the use of vitamin K antagonists is associated with increased coronary and cardiac valve calcification [15,16]. Studies on the relationship between coronary artery calcification and MGP gave conflicting results [17,18]. In this respect, vitamin K status may be of importance as studies with vascular smooth muscle cells have shown that MGP production is triggered by extra cellular calcium [19].…”
Section: Introductionmentioning
confidence: 99%
“…63 In patients with coronary heart disease and vascular wall calcifications, serum MGP levels were significantly reduced in comparison with patients without calcifications. 94 Vitamin K deficiency as a result of either malnutrition or systemic use of anticoagulants such as warfarin may possibly lead to vascular wall calcification. 88 Regardless of the mechanism involved, MGP constitutes an important inhibitor of vascular calcification and mineral precipitation, suggesting that it serves as a major vascular and bone homeostasis modulator.…”
Section: Matrix Gla Protein (Mgp)mentioning
confidence: 99%